The Improving students’ cognitive skill: The use of the project-based learning of STEM Model - Ita Tri Lestari; Unik Ambarwati; Tri Asih (JINoP (Jurnal Inovasi Pembelajaran), 2024)
Science learning emphasises the provision of direct experience to develop students’ competencies in exploring and understanding the natural surroundings scientifically. However, the science learning process in SDN 2 Bulusan, Indonesia, remains directed at students’ ability to merely remember various information without relating it to their natural surroundings. This impacted students’ ability to understand science only to the extent of rote memorisation. There is a need for an approach that improves students’ cognitive skills to achieve the desired ability. The objectives of this study are: (1) to explain the procedures of Project-based Learning (PjBL) in teaching Science, Technology, Engineering, and Mathematics (STEM); and (2) to improve scientific attitudes and students’ cognitive learning outcomes. This research employed classroom action research (CAR) with two cycles for 13 fifth graders of SDN 2 Bulusan. The data was obtained through interviews, observation, and tests, which were analysed using source triangulation and technique triangulation. The results showed that: (1) PjBL STEM was carried out through reflection, research, discovery, application, and communication; and (2) students’ cognitive learning outcomes have increased as shown through minimum completion criteria, which improved from 76.9% to 92.3%. This finding shows that PjBL STEM potentially improves the cognitive learning outcomes of Indonesian fifth-graders.